DEVELOPMENT AND EVALUATION OF CHITOSAN HONEY HYDROGEL SHEETS AS WOUND DRESSING - L.SASIKALA; BHAARATHI DURAI (International Journal of Pharma and Bio Sciences, 2015)
Multiplication of antibiotic resistant bacteria complicates the wound healing process nowadays. It has been proved that our ancient medicine honey is a panacea for a lot of diseases and it plays a vital role in wound healing. Hydrogel sheets were developed from chitosan and chitosan-honey in this study to evaluate the required properties for effective wound dressings, such as, folding endurance, degradation, water vapour transmission, swelling ratio, tensile strength, elongation, antimicrobial property and animal study. Based on the Minimum Inhibition Concentration (MIC) value of Manuka honey (Leptospermum scoparium), 8% concentration of honey was experimented. The hydrogel sheets were produced from chitosan(C) and chitosan-honey (CH) with lactic acid as solvent. The CH sample showed significant results in physical properties and mechanical properties. It also showed higher zone of inhibition against Staphylococcus aureus and Escherichia coli, the most wound infecting bacteria and contributed significantly to excision wound healing with 94.4% wound contraction on 12th day. The sheet was also soft, flexible and exhibits its potential to be used as a wound dressing.